The role of Posyandu in the Prevention of Early Childhood Stunting - Islamiati, Desta; Kurniasih, Siti (JURNAL PENA PAUD, 2025)
Posyandu plays a crucial role in reducing the incidence of early childhood stunting. The issue of stunting in Indonesia remains a significant concern today. Stunted children experience barriers to physical and mental development due to chronic malnutrition, which manifests as short stature and impaired IQ. This study aims to determine the role of posyandu in preventing early childhood stunting in Mandah Village, Natar District, South Lampung. Observation, interview, and documentation methods are used to collect data in descriptive qualitative research. Data were obtained from primary and secondary sources. Cadres, village midwives, and one Posyandu participant acted as informants. Data analysis techniques, utilizing Miles and Huberman models, encompass data collection, data reduction, data presentation, and concluding. The results showed that the role of Posyandu in the Prevention of Stunting in Mandah Village, Natar District, South Lampung is said to be good because the program is run per the standards of the number of fundamental skills of cadres, such as supplementary feeding (PMT), vitamin complementary feeding, giving appetite syrup for toddlers, giving tablets added Blood (TTD) for pregnant women, immunization, monitoring the growth of toddlers, home visits and stunting Hazard counseling.